2017
DOI: 10.2147/ppa.s127139
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with chronic hepatitis B during antiviral treatment and off-treatment

Abstract: IntroductionHealth-related quality of life (HRQoL) has emerged as an important consideration in the care of patients with chronic hepatitis B (CHB). However, whether benefits from the improved HRQoL that occurs after antiviral treatment or drug discontinuation outweigh the risks of viral relapse is an unanswered question. The aim of this study was to evaluate the HRQoL among patients with CHB during antiviral treatment and withdrawal of treatment.Patients and methodsThere were 102 patients who met the enrollme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 27 publications
(30 reference statements)
0
44
0
1
Order By: Relevance
“…But the mechanisms of carcinogenesis are different compared with NBNC-HCC [20,22]. HBV is a DNA virus that causes malignant transformation of hepatocytes mainly through gene integration into chromosomes and activation of oncogenes [25][26][27][28]. The mechanism of NBNC-HCC is still unclear, and metabolic factors may be an important factor [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…But the mechanisms of carcinogenesis are different compared with NBNC-HCC [20,22]. HBV is a DNA virus that causes malignant transformation of hepatocytes mainly through gene integration into chromosomes and activation of oncogenes [25][26][27][28]. The mechanism of NBNC-HCC is still unclear, and metabolic factors may be an important factor [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that CHB, NAFLD, and MetS lead to the development of liver fibrosis, cirrhosis, and HCC. [22][23][24] A prospective study from Taiwan indicated that a high BMI at baseline correlated with the incidence of liver cirrhosis and HCC. 25 In our study, we found that CHB patients with MetS components had accelerated rates of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…These agents are aimed at inhibiting the reverse transcription of pregenomic RNA with suppression of HBV replication . However, complete eradication of HBV infection is difficult because of the nature of HBV replication . Hence, patients have required regular follow‐ups to monitor their liver condition during antiviral treatment, especially when they progressed into liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, complete eradication of HBV infection is difficult because of the nature of HBV replication. [25][26][27] Hence, patients have required regular follow-ups to monitor their liver condition during antiviral treatment, especially when they progressed into liver fibrosis. Liver biopsy has been recommended as the reference standard for evaluating the degree of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%